MENEMUKAN MAKNA DALAM KETIDAKPASTIAN - Armin Nasution (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
In order for us to be more calm, I am convinced that we must use all our abilities to continue the future figure. That's what I'm trying to do. I want to show that however there is a meaning in all things that seem meaningless, which surrounds us. You see, the picture might seem chaotic, but "chaos" is not the right word to describe this reality. In physics, chaos is not true. Khaos actually states that there is a pattern underlying theality; and there are reasons why certain things happen. However, among those reasons there is space, there is a chance, so you can do something different in terms of things. And that's what really excites me in the midst of all the uncertainties, even anarchy, that are happening around us. Why because it means that the future is not entirely determined. Even in physics the events are not entirely determined¬ which means that the soft flapping of a butterfly's wing or whatever I do, how small it is can really change the world even if only a little.